Two new species of the genus Criotettix Bolivar, 1887 (Orthoptera: Tetrigidae: Scelimeninae) from India - Gupta, Sunil Kumar; Chandra, Kailash (Zootaxa, 2018)
Two new species i.e. Criotettix gidhavensis sp. nov. and Criotettix gariyabandicus sp. nov. are described from Sitanadi Wildlife Sanctuary, and Udanti Wildlife Sanctuary, Chhattisgarh, India. Distribution map and a key to the Indian species of the genus Criotettix Bolivar, 1887 are also provided.